Framing the Role of and Defining Criteria for Usefulness of Citizen Satisfaction Surveys in Local Urban Environmental Management: The Case of the Local Government Unit of Quezon City, Philippines - Labaria, Elirozz Carlie D (Archīum Ateneo, 2017)
The delivery of urban environmental services is among the functions devolved to local governments. As public services, they are routinely evaluated typically using ‘hard’ performance measures. The current trend of local governance incorporates citizens’ perspectives in assessing service performance. In this study, the importance and ‘usefulness’ of citizen satisfaction surveys in local urban environmental management are explored using the case of the local government of unit (LGU) of Quezon City, Philippines and its experience with the Citizen Satisfaction Index System (CSIS). For Quezon City, citizen satisfaction ratings are an important indication of city performance. For the Environmental Protection and Waste Management Department (EPWMD), data and information is considered ‘useful’ if it is (1) able to help craft the future directions of the Department, (2) able to help identify the services that can be removed, (3) able to reflect actionable community feedback, (4) presented in the form of disaggregated data and evidence and (5) easy to interpret by the users. In applying the criteria to evaluate the data and information generated from the CSIS 2014 and 2016, the study demonstrates the merits of using ‘soft’ performance measures in appraising and improving local urban environmental services.